A combined study of radar facies, lithofacies and three‐dimensional architecture of an alpine alluvial fan (Illgraben fan, Switzerland). Issue 1 (18th August 2014) - Franke, Daniel; Hornung, Jens; Hinderer, Matthias; Mountney, Nigel
Abstract Alluvial fans serve as useful archives that record the history of depositional and erosional processes in mountainous regions and thus can reveal the environmental controls that influenced their development. Economically, they play an important role as groundwater reservoirs as well as host rocks for hydrocarbons in deeply buried systems. The interpretation of these archives and the evaluation of their reservoir architecture, however, are problematic because marked heterogeneity in the distribution of sedimentary facies makes correlation difficult. This problem is compounded because the accumulated sedimentary deposits of modern unconsolidated fan systems tend to be poorly exposed and few such systems have been the focus of investigation using high‐resolution subsurface analytical techniques. To overcome this limitation of standard outcrop–analogue studies, a geophysical survey of an alpine alluvial fan was performed using ground‐penetrating radar to devise a scaled three‐dimensional subsurface model. Radar facies were classified and calibrated to lithofacies within a fan system that provided outcropping walls and these were used to derive a three‐dimensional model of the sedimentary architecture and identify evolutionary fan stages. The Illgraben fan in the Swiss Alps was selected as a case study and a network of ca 60 km sections of ground‐penetrating radar was surveyed. Seven radar facies types could be distinguished, which were grouped into debris‐flow deposits and stream‐flow deposits. Assemblages of these radar facies types show three depositional units, which are separated by continuous, fan‐wide reflectors; they were interpreted as palaeo‐surfaces corresponding to episodes of sediment starvation that affected the entire fan. An overall upward decline in the proportion of debris‐flow deposits from ca 50% to 15% and a corresponding increase in stream‐flow deposits were identified. The uppermost depositional unit is bounded at its base by a significant incision surface up to 700 m wide, which was subsequently filled up mostly by stream‐flow deposits. The pronounced palaeo‐surfaces and depositional trends suggest that allocyclic controls governed the evolution of the Illgraben fan, making this fan a valuable archive from which to reconstruct past sediment fluxes and environmental change in the Alps. The results of the integrated outcrop–geophysical approach encourage similar future studies on fans to retrieve their depositional history as well as their potential reservoir properties.